Hubungan Perilaku Picky Eater dengan Status Gizi (BB/U) Anak Usia 2-5 Tahun di Wilayah Kerja Puskesmas Anggut Atas Kota Bengkulu Tahun 2018 - Sinta Wahyu Lestari; Betty Yosephin Simanjuntak; Desri Suryani (Jurnal Vokasi Kesehatan, 2019)
Toddler age is a period of rapid growth and development. Picky eater occurs a lot at the age of toddlers and twice the risk to have a lower weight than children who are not picky eater. The purpose of this study was to determine the relationship of picky eater behavior with nutritional status (BB / U) of children age 2-5 years in the working area of Puskesmas Anggut Atas Bengkulu.This research uses analytic observational with cross sectional design. The number of samples of 70 children aged 2-5 years in the Work Area of Puskesmas Anggut Atas Bengkulu. Univariate and bivariate data analysis with chi square statistical test.The result that nutritional status based on BB / U of normal category was 75.7% and picky eater behavior was 58.6% while the statistical test showed probability (p) of 0.981 (p <0.05). There is no correlation between picky eater behavior with nutritional status (BB / U) of children aged 2-5 years in the work area of Puskesmas Anggut Atas Bengkulu. Consultation and counselingÂ  is needed to parents who have children under five, so that voter behavior can be changed.